The Role of Microfinance in Fostering Entrepreneurship and Economic Growth in Indonesia - Judijanto, Loso; Sudiana, Urip (The Es Economics and Entrepreneurship, 2025)
This study explores the role of microfinance in fostering entrepreneurship and economic growth in Indonesia through a qualitative analysis involving five informants, including microfinance practitioners, entrepreneurs, and policymakers. The findings reveal that microfinance plays a pivotal role in providing financial resources, encouraging entrepreneurial behavior, and supporting job creation, thereby stimulating local economic development. However, challenges such as high interest rates, limited outreach, and low financial literacy among clients hinder its full potential. Recommendations include enhancing financial literacy programs, leveraging technology to expand access, and introducing supportive policies to reduce costs. The study highlights the need for collaborative efforts to optimize the benefits of microfinance for national economic growth.